2013
DOI: 10.1016/j.str.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Conformational Dynamics Are Coupled to Catalysis in the mRNA Decapping Enzyme Dcp2

Abstract: Summary Removal of the 5′ cap structure by Dcp2 is a major step in several 5′–3′ mRNA decay pathways. The activity of Dcp2 is enhanced by Dcp1 and bound coactivators, yet the details of how these interactions are linked to chemistry are poorly understood. Here we report three crystal structures of the catalytic Nudix hydrolase domain of Dcp2 that demonstrate binding of a catalytically essential metal ion, and enzyme kinetics are used to identify several key active site residues involved in acid/base chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
3
27
0
Order By: Relevance
“…Immunopurified GFP–DCP2 exhibited decapping activity (Figure 6A, lanes 2–4 and Figure 6B), as reported previously (4,16). This activity was specific because a DCP2 protein variant that carries a glutamine substitution in one of the four catalytic glutamates (E148Q) was strongly impaired (Figure 6A, lanes 5–7 and Figure 6B), as expected (4,9,33). A western blot carried out with the corresponding samples showed that wild-type DCP2 and the E148Q mutant interacted with DCP1 and EDC4 to comparable levels and that equivalent amounts of immunoprecipitated DCP2 were present in the decapping reaction (Figure 6C, lanes 2 and 3).…”
Section: Resultssupporting
confidence: 63%
“…Immunopurified GFP–DCP2 exhibited decapping activity (Figure 6A, lanes 2–4 and Figure 6B), as reported previously (4,16). This activity was specific because a DCP2 protein variant that carries a glutamine substitution in one of the four catalytic glutamates (E148Q) was strongly impaired (Figure 6A, lanes 5–7 and Figure 6B), as expected (4,9,33). A western blot carried out with the corresponding samples showed that wild-type DCP2 and the E148Q mutant interacted with DCP1 and EDC4 to comparable levels and that equivalent amounts of immunoprecipitated DCP2 were present in the decapping reaction (Figure 6C, lanes 2 and 3).…”
Section: Resultssupporting
confidence: 63%
“…These strains, dubbed dcp2-E153Q-N245 and dcp2-E198Q-N245 , harbor the same dcp2-N245 allele but each also contains one additional function-inactivating mutation in an active site residue of the Dcp2 Nudix domain, i.e., glutamate (E) to glutamine (Q) substitutions at codon positions 153 and 198, respectively. E153 of Dcp2 has been shown to function as a general base during the hydrolysis reaction and E198 is involved in Mg 2+ coordination within the Nudix domain (Aglietti et al, 2013). E153Q and E198Q mutations essentially eliminate the decapping activity of Dcp2 both in vitro and in vivo ( Aglietti et al, 2013, He and Jacobson, 2015a ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the decreased steady-state accumulation of YRA1 pre-mRNA in edc3Δdcp2Δ cells harboring the dcp2-N300 or N245 allele is directly attributable to increased decapping activity, we generated dcp2-N245 alleles harboring mutations in catalytically important residues, including those functioning as general acid (K135A) or general base (E153Q), or involved in metal-binding (E198Q) (Aglietti et al 2013), and analyzed the effects of these mutations in YRA1 premRNA decay in dcp2Δ and edc3Δdcp2Δ cells. In contrast to the unmodified dcp2-N245 allele, the dcp2-N245 alleles harboring each of these amino acid substitutions failed to promote YRA1 pre-mRNA decay and resulted in the increased accumulation of YRA1 pre-mRNA in both dcp2Δ and edc3Δdcp2Δ cells (Fig.…”
Section: Resultsmentioning
confidence: 99%